Olhar para o “fim do mundo”: diálogo com famílias engajadas sobre o impacto das imagens da crise - Santilli, Ana Catarina (2023)
Amidst the crisis of planetary sustainability caused by human actions, it is important to think about the way in which human beings look at and relate to the planet, and about the dialogue that adults can try to establish with future generations, aiming for a more ecological worldview. Given this concern, the present research aimed to talk to children, teenagers, fathers and mothers who are involved, to some degree, with environmental activism, with the expectation of understanding how they can look, process and make sense of the ecological catastrophe images that surround them. The intention of this work was to capture the types of images capable of moving, sensitizing and boosting each person's activism, considering the importance of intergenerational dialogue in the family environment, which houses and provides the first world models for a child to give cohesion to the environment and to position itself in the world. From there, the following question was raised: How is it possible to face and process the chaotic images of a crisis that threatens to extinguish various ways of life on Earth, and how can fathers and mothers help their children to do the same, in order to transform the way how they perceive and relate to the world? To try to answer this complex question, a qualitative field research was carried out, based on interviews with families concerned about the environmental crisis and who are looking for ways to reverse the catastrophic path the planet is heading towards. This research was based on the hypothesis that, in the search for a more ecological world, a more ecological communication is necessary, in which we can perceive the others (human and nonhuman) with whom we interact, not as objects, but as subjects in a relationship of otherness. In this way, the statements collected in the field research were placed in dialogue with the thoughts of authors who study communication and culture in an ecological way, based on three theoretical axes. First: the ecology of images proposed by Norval Baitello, who understands images as a sensorial complex, with a strong power of impact, which is not exclusively in external objects, nor within our mind, but in the “in between”. Second: archetypal psychology initiated by James Hillman, who perceives how the human soul is entangled in the soul of the world, and how our psyche instinctively links with its environment through images. Third: the philosophy of Vilém Flusser, who captures the feeling of “emptiness” that invaded us at the end of the Modern Era, and proposes intersubjectivity and dialogue as ways to giving meaning to the shared world. From the field research and the proposed theoretical framework, it was possible to verify the need for constant dialogue with others to process such terrifying images and perceive oneself as part of a planet in crisis; in addition to the importance of a soulful gaze, capable of restoring soul to the surroundings, linking us affectively to the living world, rescuing vital emotions, and attributing profound meaning to a struggle that can so often seem absurd